2014
DOI: 10.1016/j.envpol.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of PAH concentrations and stable isotope signatures (δ13C, δ15N) in mosses from three European areas – Characterization by multivariate analysis

Abstract: Polycyclic aromatic hydrocarbon (PAH) concentrations and N, C stable isotope signatures were determined in mosses Hypnum cupressiforme Hedw. from 61 sites of 3 European regions: Île-de-France (France); Navarra (Spain); the Swiss Plateau and Basel area (Switzerland). Total PAH concentrations of 100-700 ng g(-1), as well as δ(13)C values of -32 to -29‰ and δ(15)N values of -11 to -3‰ were measured. Pearson correlation tests revealed opposite trends between high molecular weight PAH (4-6 aromatic rings) content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Previous studies have stated that the death rates from some diseases (e.g., lung cancer, cardiovascular) are usually correlated with some topographic factors, such as numerical elevation or altitude [ 30 , 31 , 32 , 33 , 34 ]. The current study also demonstrated that spatial variations of lung cancer mortality in Xuanwei were quantitatively associated with topographic characteristics at the village scale.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have stated that the death rates from some diseases (e.g., lung cancer, cardiovascular) are usually correlated with some topographic factors, such as numerical elevation or altitude [ 30 , 31 , 32 , 33 , 34 ]. The current study also demonstrated that spatial variations of lung cancer mortality in Xuanwei were quantitatively associated with topographic characteristics at the village scale.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, biomonitors like conifer needles (Ratola et al, 2010), deciduous leaves (De Nicola et al, 2013), lichens (Blasco et al, 2011) and mosses/bryophytes (Foan et al, 2014) can be a useful strategy to monitor the exposure of wildlife and human populations to these pollutants. Due to the lack of root system and cuticle, as well as their high cationic exchange capacity and surface area to volume ratio, mosses are excellent subjects for biomonitoring (Harmens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For ectohydric moss species, the lack of a well-developed root system, vascular system and protective cuticle means that they receive and take up water, nutrients and contaminants mainly from atmospheric deposition (dry, wet and occult). Hence, such mosses have shown to be suitable indicators of atmospheric deposition of, for example, nitrogen (Harmens et al, 2011;Pitcairn et al, 2006;Salemaa et al, 2008;Solga et al, 2005;Zechmeister et al, 2008), heavy metals (Harmens et al, 2010;Harmens et al, 2012;Schröder et al, 2010b) and selected persistent organic pollutants (Foan et al, 2010(Foan et al, , 2014Harmens et al, 2013a). The moss monitoring technique provides a complementary, time-integrated measure of element deposition from the atmosphere to terrestrial systems.…”
Section: Introductionmentioning
confidence: 99%